Beyond access: assessing WASH service delivery models in healthcare facilities of North Mecha, Dera, and Farta, Ethiopia - Abireham Misganaw Ayalew (BMC Health Services Research)
Abstract Background The provision of Water, Sanitation, and Hygiene (WASH) services in Healthcare Facilities (HCFs) necessitates more than just infrastructure; it requires a comprehensive systems approach. Effective WASH service delivery in HCFs involves establishing clear and practical policies and strategies, institutional arrangements and capacity, accountability mechanisms, as well as financing, planning, and monitoring. However, there is currently no well-defined service delivery model for WASH in HCFs in Ethiopia. Objective The objective of this assessment is to gather evidence on the WASH service delivery models in healthcare facilities of North Mecha, Dera, and Farta Woredas of the Amhara Region in 2023. Methods This assessment employed a mixed study design (incorporates both a cross-sectional survey and qualitative method) utilizing both qualitative and quantitative methods specifically desk review, focus group discussion, key informant interview, observation and citizen (client/patient report card data collection methods were employed to collect the data. A total of 384 citizens were selected through a systematic random sampling technique to participate in the survey. Qualitative data were collected from the Amhara Regional WASH Bureaus (Water & Health) and the targeted Woreda WASH sector offices. Data collection was facilitated using the mWater application and analyzed with Excel and SPSS data analysis software. As exclusion criteria, we are not considering households not visiting the HCFs and all health facilities except health centers. Results Healthcare Facilities WASH, Infection Prevention and Control/Clean and Safe Healthcare Facility (IPC/CASH), and Ethiopian Health Centers Reform Implementation are the policy documents that govern the provision of WASH in HCFs. The service providers (HCFs), however, are neither aware of them nor fully comprehend them. Common water sources for healthcare facilities (HCFs) included shallow wells equipped with solar power and utility connections. The sanitation technologies employed were ventilated improved latrines and pour flush systems. Hygiene services were made accessible through both fixed and mobile handwashing devices; however, many of these devices were non-functional during our visit. All HCFs implemented a three-bin waste collection system, with disposal methods involving incinerators and secured dump pits. Despite these measures, the facilities were unable to deliver the intended services due to inadequate operation and maintenance. Each HCF employed cleaners to maintain the cleanliness of rooms, compounds, and linens, although the number of cleaners (2–3 per HCF) was significantly lower than the national standard of 10 cleaners per HCF. HCFs reported having sufficient personal protective equipment. According to the citizen report card assessment results, only 12% of respondents were aware of all WASH service standards in HCFs, and merely 16% believed the current services were of adequate quality. While sanitation and waste management services were generally rated as adequate, water and hygiene services were predominantly rated as inadequate, rendering them unsatisfactory. Most respondents rated the overall cleanliness of the HCFs as fair and expressed low satisfaction with the level of service. The primary causes of dissatisfaction included the low cleanliness of the facilities, lack of inclusiveness of services, service disruptions, and inadequacy. Conclusions In contrast to household settings, healthcare facilities (HCFs) lacked a distinct model for WASH service delivery. Although the Ministry of Health developed various guidelines, significant implementation gaps were identified during the assessment. These gaps include the duplication of guidelines, the absence of a fully accountable individual at the healthcare facility level for operations and maintenance according to standards, the lack of a specific plan and adequate budget, insufficient spare parts, and low citizen engagement. Additionally, Woreda and Region provided inadequate support due to budgetary constraints. Unlike private healthcare service providers, where the policymaker, service provider, and regulator are distinct entities, all these roles fall under the same Ministry, resulting in lax enforcement of existing standards.